2012
DOI: 10.1111/exd.12029
|View full text |Cite
|
Sign up to set email alerts
|

A specific combination of zeaxanthin, spermidine and rutin prevents apoptosis in human dermal papilla cells

Abstract: cer (30) give rise to future applications of 2D pH sensors in studying tumor metabolism. AcknowledgementsThis work was supported by grants from the German Research Foundation DFG (grants BA3410/4-1 and WO669/9-1). Traumasept Wound Gel was supplied by Dr. August Wolff GmbH & Co. KG (Bielefeld, Germany). Author contributionsS.S., R.J.M., O.S.W. and P.B. conceived the experiments. S.S., R.J.M., K.T.W., J.C. and D.F. performed the experiments. S.S., R.J.M. and D.F. analysed the data. S.S. and R.J.M. wrote the pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
5
0
2
Order By: Relevance
“…ZD treatment evidently reduced the apoptotic ratio through restoring Bcl-2 expression and reducing caspase activity. These data supported the beneficial effects of ZD on the liver by improving the anti-apoptotic response, which was consistent with a recent study showing the anti-apoptotic function of zeaxanthin through Bcl-2 and MAPK in human dermal papilla cells [30].…”
Section: Discussionsupporting
confidence: 92%
“…ZD treatment evidently reduced the apoptotic ratio through restoring Bcl-2 expression and reducing caspase activity. These data supported the beneficial effects of ZD on the liver by improving the anti-apoptotic response, which was consistent with a recent study showing the anti-apoptotic function of zeaxanthin through Bcl-2 and MAPK in human dermal papilla cells [30].…”
Section: Discussionsupporting
confidence: 92%
“…In a study, apoptosis of human follicular dermal papilla cells was observed after treatment with staurosporine; this event was completely introverted by exposure to rutin, spermidine, and zeaxanthin. There was the preservation of expression of anti-apoptotic molecules such as Bcl-2, MAP-kinases and their phosphorylated forms, which concludes the use of rutin in the prevention of apoptosis of hair follicular cells, one of the leading causes of baldness (Carelli et al, 2012).…”
Section: Pharmacological Actionsmentioning
confidence: 88%
“…The research on herbs and active constituents as hair growth promoters has been driven by their less toxicity, easy availability, low‐cost, patient compliance and more than one mode of biochemical action . Specific effects of herbal extracts, polyherbal formulations, flavonoids and natural compounds on DPCs have been examined . In vivo hair growth promoting effects as proof of concept are also mentioned.…”
Section: Hair Growth Promoting Effectmentioning
confidence: 99%